SEGITIGA TERUMBU KARANG DUNIA (THE CORAL TRIANGLE): MANFAAT, MASALAH DAN UPAYA - Dadang Ilham Kurniawan Mujiono; Jusmalia Oktaviani (Universitas Jenderal Ahmad Yani, 2021)
The coral triangle is the epicenter of marine biodiversity in the world which located in the eastern part of Southeast Asia and the western part of the Pacific Ocean. Despite the benefit of this area, the coral triangle also faces unsustainable fishing practices called Illegal, Unreported, and Unregulated (IUU). This paper is aiming to provide the benefit of the coral triangle, and the efforts to overcome the problem that occurs in this area. To analyze this paper, the authors applied a descriptive approach, and most of the data obtained through literature review. And the result shows that the coral triangle is very beneficial to the countries in this area. Furthermore, to protect these precious natural resources from IUU, the government in this area decided to work together to overcome through the establishment of a multilateral partnership The Coral Triangle Initiative on Coral Reefs, Fisheries, and Food Security (CTI)